Agro-technical measures for rational use of moisture - Pysarenko, V.; Pysarenko, P.; Pischalenko, M.; Melnychuk, V.; Yevstafieva, V. (Scientific Progress & Innovations, 2022)
According to agroclimatic indicators, in particular, according to the indicator of moisture availability of the Steppe and Forest Steppe of Ukraine, that is, most of the territory of the state has an insufficient amount of precipitation during the growing season. Accordingly, it negatively affects the productivity of crops traditionally grown in one or another region. From an agronomic point of view, such zones with insufficient natural moisture supply become so-called arid climate zones, and therefore require special management conditions that allow obtaining consistently high yields of crops under unfavorable conditions for plants. Thus, there is a need to develop scientifically based measures that contribute to the accumulation and preservation of autumn-spring moisture reserves in the soil, as well as methods that contribute to the preservation and reduction of this moisture loss during each work operation during the growing season of agricultural crops. Therefore, the purpose of the review presented in the article is to highlight both classical and modern agrotechnical measures aimed at the rational use of moisture in soils. The article collects, analyzes and summarizes the experience of both domestic and foreign scientists, whose work is closely related to the use of agrotechnical methods aimed at reducing soil moisture loss during its cultivation in arid climates. The article is based on materials related to climate change, the possible impact of related droughts on agriculture, scientific and practical experience of using agrotechnical measures to reduce the negative impact of moisture deficit on the productivity of agricultural crops. Thus, the most effective adaptive measures are considered to be methods developed on the principles of the opposite relationship – in response to moisture deficit, measures for its conservation and rational use should be developed. Such agrotechnical techniques should be comprehensive and necessarily include techniques aimed at the formation of soil-protective moisture-saving farming systems, the organization of land territory, the structure of sown areas, rational crop rotations, soil cultivation systems, measures to combat water and wind erosion, and fertilization systems. Only in a complex, such agrotechnical measures can solve the problem of low yields of agricultural crops in the conditions of an arid climate.